Pre-Extension Demonstration of Improved Bread Wheat Varieties with Their Production Packages in High land Area of Eastern Amhara Region, Ethiopia - Abere Haile; Negussie Siyum; Mekonnen Assefa; Mesfin Bahta (Agro Bali : Agricultural Journal, 2021)
The study was basically focused on demonstration of bread wheat technologies for wider demand-driven technology diffusion in major wheat growing area in high land of eastern Amhara. The objectives were in order to evaluate and demonstrate improved bread wheat variety with their production package to the farming community and assess farmers and extension workers reaction towards improved bread wheat technology. The activity was conducted in main season 2019/2020 at Jama and Meket districts. The fact that wheat production and productivity in the region as well as in the particular study area low because farmers are using low yielding, disease and pest resistant local varieties. The improved bread wheat variety was demonstrated along with the local variety at 12 farmers' fields. Yield data, economic data, farmers’ perception and preferences were collected throughout the demonstration stages and data were analyzed by using ANOVA, partial budget analysis and preference ranking. The results of ANOVA showed that yield and yield related parameters statistically significant at the probability level of  0.01% and 0.05% among treatments. The highest mean yield was recorded from "Hibist" with improved management 2.49 ton/ha and 1.42 ton/ha at Jama and Meket districts respectively followed by local with improved management and the lowest was from local with farmers practices. Furthermore, the result of partial budget analysis show that the use of improved and local variety with recommended package more profitable with the MRR of 1.96 and 0.81 than farmer practices at Jama district and 74.26 and 9.26 at Meket district respectively. Farmer preference analysis improved & local variety with improved management ranks 1st and 2nd at Jama respectively while reverse at Meket and lastly ranks farmer practices at both districts. Generally, improved bread wheat with recommended package has higher yield advantage, financial feasibility and social acceptance than control and farmer practices, it is recommended to be scale out for further dissemination.